Body Mass Index (BMI) and Its Influence on the Cardiovascular and Operative Risk Profile in Coronary Artery Bypass Grafting Patients: Impact of Inflammation and Leptin. (24th June 2020) - Buschmann, Katja; Wrobel, Julius; Chaban, Ryan; Rösch, Romina; Ghazy, Ahmed; Hanf, Alina; Schäfer, Katrin; Daiber, Andreas; Beiras-Fernandez, Andres; Vahl, Christian Friedrich
Abstract : Background . Obesity is related to coronary artery disease (CAD) and worse outcomes in coronary artery bypass graft (CABG) patients. Adipose tissue itself is an endocrine organ that secretes many humoral mediators, such as adipokines, which can induce or reduce inflammation and oxidative stress. Objectives . We investigate the relationship between the body mass index (BMI), inflammation, and oxidative stress by measuring serum levels of leptin, interleukin-6, and 3-nitrotyrosine in CABG patients and correlate their levels to the cardiovascular and operative risk profiles. Methods and Results . 45 men (<75 years) with a median BMI of 29 (21-51) kg/m 2, who were diagnosed with CAD and scheduled for elective CABG, were included after applying the following exclusion criteria: prior myocardial infarction, reoperation, female gender, and smoking. Patients' blood samples were taken preoperatively. Several markers were measured. We found significant correlations between leptin and BMI p < 0.0001 as well as between leptin and 3-nitrotyrosine p = 0.006 . Interleukin-6 was correlated with C-reactive protein p < 0.0001 and with the incidence of insulin-dependent diabetes mellitus p = 0.036, arterial hypertension p = 0.044, reduced left ventricular function p = 0.003, and severe coronary calcification p = 0.015 . It was also associated with significantly longer extracorporeal bypass time p = 0.009 . Postoperative deep sternal wound infections could be predicted by a higher BMI p = 0.003 and leptin level p = 0.001 . Conclusions . There seems to be a correlation between inflammatory processes and cardiovascular morbidity in our cohort. Further, the incidence of deep sternal wound infections is related to a higher BMI and leptin serum level.